Pelatihan Pengelolaan dan Pelaporan Keuangan Desa - Rumintar J.H. Marpaung; Thomas Averio (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
Village financial management is something that really needs to be considered in its implementation. In Law No. 6 of 2014, it is explained that 10 percent of the source of funds for village management comes from the APBN. The 10 percent allocation from the APBN will increase village fund revenues. Village funds provided by the central government aim to encourage the productivity of rural communities. This increasing village fund receipt requires good village financial management, namely the need to prepare financial reports and accountability reports from the village in accordance with the guidelines in government regulation no. 113 of 2014, namely village financial management is all activities which include planning, implementation, administration, reporting and accountability of village finances. The aim of implementing this community service (PKM) is to provide adequate knowledge and training to village officials in Semanget village regarding the management and financial reporting of village funds in a good, transparent, accountable, participatory, orderly and budget discipline manner in accordance with Permendagri Number 113 of 2014, Apart from that, this community service is also useful in early prevention of potential misappropriation of village funds so that village fund managers can avoid legal problems in the future.